ISLAM DAN PEMBAURAN SOSIAL: REKONSTRUKSI FENOMENA MULTIKULTURALISME - Aqil Irham (Islam Realitas: Journal of Islamic and Social Studies, 2015)
Islam, as religion which has a universal concept, views that assimilation is inhern (traits) which stands in every individu, thus, in the next stage also dwells in every human group as the group of individuals themselves. The relationship between Islam and assimilation is absolute; it can be seen in al Hujurat: 13 which mean that the necessity for human to socialize or assimilate. In addition, the meaning of the verse is the design of God about pluralism in the present context and review by using the term of multiculturalism. Assimilation requires the interrelatedness of understanding and mutual respect of differences as a thing that must be upheld, because only with mutual respect the assimilation will be carried out responsibly and dignityly. In contrary, without promoting respect for differences in attitude, the assimilation could certainly have a lot of problems; even tends to face competition wrapped by hyphocretism. ebagai agama yang memiliki konsep universal, Islam berpandangan bahwa pembauran merupakan sesuatu yang inhern (sifat bawaan) yang ada pada setiap individu manusia, sehingga pada tahapan selanjutnya juga bersemayan pada setiap kelompok manusia yang merupakan kumpulan dari individu-individu itu sendiri.  Hubungan antara Islam dan pembauran merupakan sesuatu yang mutlak, hal ini bisa dilihat dalam surat al Hujurat :13 yang bermakna keharusan bagi manusia untuk bersosialisasi atau melakukan pembauran. Selain itu, makna dari ayat tersebut adalah adanya design Allah tenang pluralisme yang dalam konteks kekinian di kaji dengan menggunakan term multikulturalisme. Pembauran menuntut adanya kesaling pemahaman dan saling menghargai adanya perbedaan sebagai suatu yang harus dijunjung tinggi, sebab hanya dengan adanya sikap saling menghargai tersebut, pembauran akan dapat dilaksanakan secara  bertanggung jawab  dan bermartabat.  Sebaliknya, tanpa mengedepankan sikap penghargaan terhadap perbedaan, maka pembauran bisa dipastikan akan banyak mengalami kendala bahkan cenderung terjadi kompetisi yang dibaluti hipokretisme.